Assessment of Prosthodontic and Orthodontic Treatment Needs among Individuals with special needs in Mysuru city, Karnataka, India - Pradeep S 17PDM044; Dr M R Dhakshaini (JSS AHER, Mysuru JSS DC, Mysuru, 2024)
1. Abstract, 2.Introduction, 3. Need for the Study /Background of the Study, 4.Aims & Objectives of Research work, 5.Review of Literature 6.Methodology,7.Statistical analysis/Results, 8.Discussion 9. Conclusion, 10.References.
Keywords: Prosthodontics and Crown Bridge